2010
DOI: 10.1007/s11251-010-9160-3
|View full text |Cite
|
Sign up to set email alerts
|

Supporting learning from illustrated texts: conceptualizing and evaluating a learning strategy

Abstract: Texts and pictures are often combined in order to improve learning. Many students, however, have difficulty to appropriately process text-picture combinations. We have thus conceptualized a learning strategy which supports learning from illustrated texts. By inducing the processes of information selection, organization, integration, and transformation, the learning strategy should lead to a more elaborated learning. After conducting a pilot study, a main study with 133 sixth-grade students from two different m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 35 publications
3
32
0
Order By: Relevance
“…This finding is substantially in line with previous eye-tracking studies with grade level students, which revealed that longer integrative processing is related to more successful deep learning when reading an illustrated science text . The finding also substantially confirms outcome-focused studies on the effectiveness of teaching reading strategies for an illustrated text to lower secondary school students (Schlag & Ploetzner, 2011).…”
Section: Transfersupporting
confidence: 76%
See 2 more Smart Citations
“…This finding is substantially in line with previous eye-tracking studies with grade level students, which revealed that longer integrative processing is related to more successful deep learning when reading an illustrated science text . The finding also substantially confirms outcome-focused studies on the effectiveness of teaching reading strategies for an illustrated text to lower secondary school students (Schlag & Ploetzner, 2011).…”
Section: Transfersupporting
confidence: 76%
“…We focused on modeling a learning task that entails much more than perceptual processes, that is, learning from words and pictures. According to theoretical models of text and picture comprehension (Mayer, 2009;Schnotz, 2002), as well as outcomefocused (Bartholomé & Bromme, 2009;Schlag & Ploetzner, 2011) and process-focused studies , the integration of verbal and pictorial representations is essential to learning from an illustrated text. In order to foster students' integrative processing, a novel approach was adopted using eye-tracking technology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both theories, the processes of information selection, information organization, information transformation, and information integration are regarded as being essential for successful learning from multimedia. Schlag and Ploetzner (2011) have conceptualized a cognitive strategy for learning from illustrated texts. The strategy aims to stimulate, sustain, and support the cognitive processes of information selection, information organization, information integration, and information transformation that are considered to be important for successful learning in Mayer's (2009) Cognitive Theory of Multimedia Learning.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Schlag & Ploetzner, 2011). In both studies, the learning material and the learning strategy were provided to the students in print.…”
Section: Interactive Learning Environmentsmentioning
confidence: 99%